SOSIALISASI DAN PELATIHAN PENERAPAN TEKNOLOGI INFORMASI DALAM BIDANG PENDIDIKAN PADA MASYARAKAT PEKON BANDUNG BARU - Trisnawati; Muhamad Muslihudin; Atif Sidqi; Leni Anggraini (Jurnal PkM Pemberdayaan Masyarakat, 2021)
The development of science and technology today is so rapidly, making information systems have a vital role in trying to make progress in all areas of human life. As one of the areas that take advantage of technological advances, developments in education are certainly happening. Recognizing this, a movement is needed to introduce and provide further deepening to the community about the application of information technology developments in the field of education, especially in the people of Pekon Bandung Baru. This socialization and training aims to provide understanding to the public about the application of information technology in the field of education.